Death of the secret recipe: “Open source cooking” and field organization in the culinary arts. - Borkenhagen, Chad (Poetics, 2017)
Knowledge sharing is an important but understudied aspect of the formation and organization of creative fields. To better understand the relationship between knowledge sharing and field organization, I examine a small but influential movement within the culinary arts known as “modernist cuisine.” This movement eschews many of the protective practices that have traditionally guarded culinary innovations in favor of an open sharing model similar to how knowledge is shared in the sciences or open source software development. Drawing on semi-structured interviews, participant observation, and other primary resources, I find that this open mode of knowledge sharing precipitates a system of peer-based citation, whereby producers receive direct recognition for their discoveries without the endorsement of traditional tastemakers such as restaurant critics. This citation-based prestige system opens the culinary field to participation from new kinds of actors, generates new roles that are better insulated from the economic demands of traditional restaurant work, and may even influence the field’s traditional status hierarchy. These findings suggest that the way knowledge is shared plays a considerable role in the organization of fields where expertise and innovation are highly valued, and that changes in these practices can have other consequences in the field at large.